Caracteres anatómicos y fitoquímicos del tallo y raíz de Mammillaria uncinata (Cactaceae) - Loza-Cornejo, Sofía; Aparicio-Fernández, Xochitl; Patakfalvi, Rita Judit; Rosas-Saito, Greta Hanako (Instituto de Ecología, A.C., 2017)
Background and Aims: Members of the Cactaceae family persist through anatomical and metabolic adaptations that allow them to develop in arid and semi-arid areas, including the synthesis of primary and secondary metabolites with specific functions. Mammillaria is a genus belonging to the Cacteae tribe and the literature on its anatomical and phytochemical characters is scarce, particularly for the species Mammillaria uncinata. Therefore, the objectives of this study were to describe the anatomical-histochemical structure and phytochemical profile of the stem and root of Mammillaria uncinata, in order to contribute to the knowledge of biology and chemical composition of the species.Methods: The study was conducted with specimens collected in their natural distribution area in the Altos Norte region of Jalisco, Mexico. The standard paraffin microtechnique and histochemical techniques were used for the description of the anatomical and histochemical characters, whereas qualitative techniques were applied to study the phytochemical profile.Key results: Laticifers and crystals of variable morphology in the stem are some of the most distinctive characters. The phytochemical profile analysis revealed the presence of abundant metabolites in the stem, including alkaloids, sterols, flavonoids and saponins, whereas in the root only the presence of sterols and saponins was detected in low amounts.Conclusions: The study showed anatomical features in Mammillaria uncinata to be similar to other Cactaceae species, as well as abundance of phytochemicals with potential application in different areas.